Assessing Ground Displacement in Oran City, Algeria: A Comparative Analysis of PSInSAR, SBAS, and Combined Method - Kamel Hasni; Bachir Gourine; Boudhane Boubaker; Slimani Mohammed El Amine (Geodetski Vestnik)
Coastal cities are grappling with ground deformation, making monitoring the temporal evolution of ground subsidence crucial. Advanced interferometric techniques, such as PSInSAR and SBAS provide a pertinent mean to observe this phenomenon by supplying dense displacement measurements for an extended period. However, while these algorithms have proven their effectiveness in some areas, their performance is less consistent in others. As such, there is a growing need to enhance the quality of displacement estimation through the development of new combination methods. In this study, Envisat images were used to assess the measurement quality of the displacement over Oran city using PSInSAR, SBAS, and a fusion technique from 2003 to 2010. Our findings indicate that PSInSAR and SBAS techniques mean velocities have similar values, ranging from -2.8 to 4.4 mm/yr and -4.6 to 4 mm/yr, respectively. Though, PSInSAR demonstrated a good distribution in urban areas and a greater precision, with a maximum standard deviation of 1.4 mm/yr, compared to SBAS that performed well in rural areas and which had a maximum standard deviation of 3.6 mm/yr. The combination method outcome was denser with a higher number of detectable pixels. Its mean velocity ranged from -4.6 to 4.2 mm/yr, with a better distribution in both urban and rural areas. Overall, the combination technique estimated displacements with better precision than the other methods, highlighting its potential as an effective tool for monitoring ground deformation.